PENGARUH KOMPETENSI KEPRIBADIAN GURU PAK TERHADAP MOTIVASI BELAJAR SISWA KELAS VII-A DAN KELAS VII-B SMP NEGERI 2 SIPOHOLON - Erna Duma Lusiana Purba (Pusat Riset dan Inovasi Nasional, 2023)
Teacher personality competence is a personal ability that reflects a solid, steady, mature, wise, and authoritative personality, being a role model for students and having noble character. Motivation is the driving force that encourages someone to do an activity that aims to get the desired result. In relation to learning, motivation is an important thing that can encourage children to carry out the expected results, namely changes in behavior.The purpose of this study was to find out whether there was a positive and significant influence between the personality competencies of PAK teachers and the learning motivation of PAK students in Class VII-A and Class VII-B of SMP Negeri 2 Sipoholon in the 2022/2023 academic year.The research data was analyzed with the following steps: 1) Test the analysis requirements by: a) Test the relationship, it is known that rcount > rtable or 0.4174 > 0.297. This shows that there is a relationship between the personal competence of PAK teachers and students' learning motivation. From the results of the significance test of the relationship, it can be interpreted that there is a positive and significant relationship between the personality competence of PAK teachers and student learning motivation, 2) Influence test: a) The magnitude of the influence of the personality competence of PAK teachers on the learning motivation of Class VII-A and Class VII-B SMP Negeri 2 Sipoholon are: (r2) x 100% = 0.1742 x 100% = 17.42%, b) Testing the regression equation Y over X, the regression equation = 23.07+0.29X means that it is in a constant state of 23, 07, student learning motivation will increase 0.29 times the value of the personal competence of PAK teachers, c) the value obtained Fcount = 1.64 > Ftable (0.05,19.51) = 1.39, then the research hypothesis is accepted.